A Search For Integral Solutions To The Ternary Bi-Quadratic Equation - et. al., S. Vidhyalakshmi, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This paper deals with the problem of obtaining non-zero distinct integer solutions to the ternary bi-quadratic equation. A few interesting relations among the solution are presented. Given on integer solution of the equation under consideration, integer solutions for various choices of hyperbola and parabolas are exhibited. The formulation of second order Ramanujan Numbers with base numbers as real integers and Gaussian integers is illustrated and also the sequence of Diophantine 3-tuples are exhibited.